Distinguishing functional exosomes and other extracellular vesicles as a nucleic acid cargo by the anion‐exchange method. Issue 3 (14th March 2022) - Seo, Naohiro; Nakamura, Junko; Kaneda, Tsuguhiro; Tateno, Hiroaki; Shimoda, Asako; Ichiki, Takanori; Furukawa, Koichi; Hirabayashi, Jun; Akiyoshi, Kazunari; Shiku, Hiroshi
Abstract: The development of a new large‐scale purification protocol is required for research on the reliable bioactivity and drug discovery of extracellular vesicles (EVs). To address this issue, herein, we propose an effective method for preparing high‐performance exosomes (EXOs) by using an anion‐exchange method. Cytotoxic T‐lymphocyte (CTL) EVs from 4 L of culture supernatant through a 220 nm cut‐off filter are divided into two populations at a deproteinization rate of over 99.97%, which are eluted at low (0.15 M–0.3 M) and high (0.3 M–0.5 M) NaCl concentrations (approximately 2 × 10 12 and 1.5 × 10 12 particles, respectively) through the anion‐exchange column chromatography. The former are abundant in EXO proteins, including late endosome‐associated proteins and rab‐family and integrin‐family proteins, and functional micro (mi) RNAs, and have bioactivity for preventing tumour metastasis by depleting mesenchymal cell populations in the primary tumour lesions. By contrast, the latter is microvesicle (MV)‐like particles including DNA, core histone and ribosomal proteins, and GC‐rich miRNAs with unknown function, and are easily phagocytosed by mannose receptor + Kupffer cells. Thus, the anion‐exchange method is suitable for the large‐scale separation of bioactive EXOs and MV‐like EVs as a cargo for dangerous nucleic acids at high‐purity.